Power/Current-based MPPT Scheme for PV Modules Operated on Wide Ambient Temperature Range - Riawan, Dedet Chandra (JAVA Journal of Electrical and Electronics Engineering, 2015)
Photovoltaic (PV) modules have non-linear characteristics described by their voltage-current relationship. At an optimum operating point of voltage and current, a PV module delivers its maximum power. The maximum power of a PV module depends on the irradiance level of sunlight and the module temperature. This paper demonstrates, through simulation and experimental verification, a method to extract maximum output power from a PV module at any irradiance level and wide range of temperature. The proposed maximum power point tracker (MPPT) is based on the power-current characteristics of a PV module. To eliminate the deviation of MPPT operation due to temperature variation, temperature compensation is added. This method yields a faster response and does not require short-circuit current or open-circuit voltage information of the module as required in constant current or voltage MPPT schemes. As the result, higher efficiency is obtained because there is no power interruption while searching the optimum point. Experimental results confirm the validity of the mathematical model and simulation of the proposed technique